The Effect of Board Structure and Institutional Ownership on Earnings Management - Wong, Shi Yang (2006)
The study examines the role of outside directors and institutional shareholders in constraining the earnings management activities.A sample of 613 firms from construction, industrial products and consumer products sectors were selected from the Main Board in Bursa Malaysia.The time period covered for this study was from 2001 to 2003.The Modified Jones Model with cross sectional approach was employed in this study.The finding shows that the magnitude of earnings management in Malaysian listed firms was approximately 16% of the previous year total assets. Most firms manage the earnings upward rather than downwards.No relationship was observed between the degree of earnings manipulation and the proportion of outside directors and institutional shareholders.This is inconsistent with most studies which provide evidence that outside directors and institutional shareholders are effective corporate governance mechanisms in constraining the earnings management.However,there is weak evidence to show that outside directors have some effect in curbing the earnings management in the construction sector.The findings suggest that outside directors have the ability to constrain the earnings management as indicated in the construction sector.Adding more outside directors in the board and having institutional shareholders may not reduce earnings management practices if the ownership of a firm is highly concentrated and the process of selecting outside directors is not clearly stated and transparent.